The role and significance of the developer’s operational activity in the construction sector - IVINSKYI, Yevhen (Ways to Improve Construction Efficiency, 2025)
The operational activity of a developer occupies a key position in ensuring the efficiency and stability of the construction sector. It encompasses the entire life cycle of a construction project – from initiation to commissioning – and determines the success of each implementation stage. The developer performs the functions of organizer, coordinator, and integrator, combining the management of resources, finances, risks, and quality. Modern operational activity is based on the principles of strategic flexibility, digital integration, and system-oriented management. Through the use of innovative technologies such as BIM (Building Information Modeling) and ERP (Enterprise Resource Planning), the developer creates a transparent system of planning, control, and forecasting. The development of digital platforms facilitates the integration of all participants in the construction process, improves communication efficiency, and reduces risks. Operational activity includes project, financial, risk, quality, and time management, ensuring the interconnection between the company’s strategic goals and its practical tasks at every level. A key factor of effectiveness is the developer’s ability to maintain a balance between economic feasibility, technical parameters, and social responsibility. Risk management has become an integral element of operational activity, covering the identification, assessment, insurance, and mitigation of potential threats. The integration of sustainable development principles, environmental standards, and energy efficiency into development practice forms a new management paradigm. As a result, the developer’s operational activity not only ensures the effectiveness of individual projects but also contributes to the formation of an innovative, socially responsible, and competitive construction industry. Additionally, operational activity includes the coordination of all stakeholders in the construction process – investors, contractors, architects, engineers, government authorities, and end users. A well-organized communication system allows the developer to ensure timely decision-making and coherence of actions among all project participants. In modern conditions, particular importance is given to the use of analytical platforms and business intelligence systems that make it possible to forecast market changes, model project development scenarios, and develop effective strategies for responding to external factors. The use of data management tools transforms operational activity into a dynamic ecosystem in which decisions are made based on objective information and predictive indicators.